Трансформация структуры высокоуглеродистого сплава Fe-V-C при обезуглероживании - Мовчан, А.В.; Губенко, С.И.; Черноиваненко, Е.А. (Вісник Українського матеріалознавчого товариства, 2017)
The regularities of phase and structural transformations during decarburization of a highcarbon Fe-V-C alloy were investigated. The eutectic transformation L → γ + VC is established by the method of geometric thermodynamics and metallographic analysis. That accompanied by a diffuse redistribution of the carbide-forming element ahead of the crystallization front. Decarburization in a liquid-solid state allows forming a favorable structure with VC fibers oriented perpendicular to the surface in the near-surface zone. It was established that the subsequent carburization of a pre-decarburized Fe-V-C alloy under special conditions makes it possible to obtain in the surface layer a natural composite with high wear resistance.